Korelasi antara kadar amilosa dan mutu tanak pada beberapa varietas beras - Millati, Tanwirul; Hustiany, Rini; Susi, Susi; Rahmi, Alia; Palupi, Dyah Retno; Finola, Marsya Ayu (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Starch is the main component of rice, consisting of amylose and amylopectin molecules. Amylose plays an important role in determining the quality of cooked rice, such as expansion volume, water uptake, and dissolved solids during the cooking process. Various rice varieties have varying amylose levels, categorized as high, medium, and low. High-amylose rice tends to have greater expansion volume, higher water absorption, and lower dissolved solids. The aim of this study was to determine the correlation between amylose content and expansion volume, water uptake, and dissolved solids. This research used six rice varieties, consisting of four local varieties, namely Siam Unus, Siam Mayang, Siam Cantik, and Gunung Wangi, and two superior varieties, namely IR 64 and Ciherang.The results showed that amylose content of rice ranged from 17.9% to 33.53% (low to high amylose levels). The local varieties had high amylose content, specifically Siam Unus, Siam Mayang, Siam Cantik, and Gunung Wangi, while the superior variety IR 64 had medium amylose content, and Ciherang had low amylose content. High-amylose rice exhibited greater expansion volume and water upteke, along with lower dissolved solids, while rice with low to medium amylose content showed smaller expansion volume and water uptake but higher dissolved solids.